Factors Related To The Burnout Of Heart Hospital Nurse Hasna Medika Cirebon During The Covid-19 Pandemic - Qowimah, Sirri Nahzatun; Utami, Wika Dianita; Agustina, Eva; Lusiana, Nova (International Conference on Sustainable Health Promotion, 2021)
The current Covid-19 pandemic is still occurring in Indonesia causing health workers, one of whom is a nurse who intervenes directly in the hospital at high risk of contracting the Covid-19 virus. Burnout in nurses occurs when faced with difficulties, workload, and high stress. The impact of burnout on nurses is emotional distress, dissatisfaction at work, life-threatening and safety, and can be a consequence of mental illness such as depression and even suicide. The purpose of study was to identify burnout-related factors in nurses of Hasna Medika Cirebon Heart Hospital during the Covid-19 pandemic. The study was conducted from August 4 to August 30, 2021, and is a descriptive study using a google form that is distributed to all nurses of Hasna Medika Cirebon Heart Hospital. A total of 65 nurses were involved in the study. The research instrument is the Maslach Burnout Inventory (MBI). The results showed that burnout in Hasna Medika Cirebon Heart Hospital nurses was in a low category by 33.8% and the moderate category by 66.2%. Age, gender, education and length of work are factors that cause burnout in nurses. In conclusion, most nurses show burnout at moderate levels and several factors were found to correlate with burnout. Prevention efforts are needed to reduce the risk of burnout in nurses of Hasna Medika Cirebon Heart Hospital